Benefits of breast milk according to the teachings of Islam, child psychology, and chemical science - Junitasari, Assyifa; Rahmawati, Rika; Fahmi, Irfan (Lighthouse Publishing, 2022)
Breastfeeding is one of the most important activities for child development. Breastfeeding is a very important part of the process of growing children who are strong and healthy, both physically and spiritually. Breastfeeding activities not only have an impact on providing nutrition but also on the stimulation of the psychological aspects of the breastfed baby. Islam recommends that a mother breastfeed her baby for two years. Reviewing this explanation, it is necessary to conduct research that integrates religious studies related to the study of Al-Baqoroh verse 233 with chemistry related to the content of breast milk and also with psychology that examines the psychology of children who receive breast milk for 2 years and those who do not get breast milk at all. The research method was carried out by reviewing the interpretation of the Qur'an Surah Al-Baqoroh verse 233 from various experts, examining the chemical content of breast milk from various experts, and carrying out psychiatric observations on 50 school-age children. Based on the results of a literature study related to the study of Al-Baqoroh verse 233 and the chemical analysis of breast milk content with the results of psychological analysis of children who received breast milk for 2 years, it shows that there is an association or relationship. The commands in the Qur'an are in line with the many benefits of breastfeeding, as well as effects on child psychology.